2019
DOI: 10.1186/s13045-019-0797-3
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells in hematological malignancies: friends or foes

Abstract: Myeloid-derived suppressor cells (MDSCs) are newly identified immature myeloid cells that are characterized by the ability to suppress immune responses and expand during cancer, infection, and inflammatory diseases. Although MDSCs have attracted a lot of attention in the field of tumor immunology in recent years, little is known about their multiple roles in hematological malignancies as opposed to their roles in solid tumors. This review will help researchers better understand the various characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 102 publications
1
63
0
1
Order By: Relevance
“…In their study IL-10 reduced the generation of effector CD4 and CD8 T-cells [19]. Still little is known about the mechanisms that lead to the increasing of M-MDSC, especially in the microenvironment of leukemia [20] and lymphoma [24]. Lee et al [36] found that TGF-b induced the expansion of the monocytic MDSC population, expression of immunosuppressive molecules by MDSCs, and the ability of MDSCs to suppress CD4+ T cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In their study IL-10 reduced the generation of effector CD4 and CD8 T-cells [19]. Still little is known about the mechanisms that lead to the increasing of M-MDSC, especially in the microenvironment of leukemia [20] and lymphoma [24]. Lee et al [36] found that TGF-b induced the expansion of the monocytic MDSC population, expression of immunosuppressive molecules by MDSCs, and the ability of MDSCs to suppress CD4+ T cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…The leukemic B cells achieve this mainly through the involvement of regulatory T (Treg) cells. In turn, MDSCs release IL-10 and TGF-b to exert their suppressive function by Tregs [8,20]. The origin of M-MDSC is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…M-MDSCs highly express inducible nitric oxide synthase (iNOS, also known as NOS2) through the signal transducer and activator of transcription (STAT1) signaling pathway, generating large amounts of nitric oxide (NO), whereas PMN-MDSCs produce high levels of reactive oxygen species (ROS) and less NO through the STAT3 pathway to suppress immune responses [15]. Both subtypes overexpress arginase 1 (ARG1), and both iNOS and ARG1 can reduce the concentration of arginine in the microenvironment and promote T cell apoptosis [4,[16][17][18]. In general, both M-MDSCs and PMN-MDSCs have the potential to inhibit the antitumor response, but the mechanism is not identical.…”
Section: Classification and Functional Differences Of Mdscsmentioning
confidence: 99%
“…MDSCs significantly inhibit the antitumor activity of T cells, especially cytotoxic T lymphocytes (CTLs), and also make proinflammatory cells, such as NK cells, DCs, and B cells incompetent; in addition, MDSCs induce the generation of anti-inflammatory T regs , TAMs, and Th17 cells, which remodel the microenvironment that supports tumor development [23]. MDSCs promote tumor epithelial-mesenchymal transformation (EMT) by expressing factors, such as TGFβ, IL-6, hepatocyte growth factor (HGF), and high mobility group binding (HMGB)-1, which makes tumors exhibit aggressive phenotypes with high migration ability [16]. In addition, MDSCs establish a premetastatic niche (pMN) for tumor development [24].…”
Section: Immunosuppressive Activity Of Mdscs In the Tmementioning
confidence: 99%
“…Multiple myeloma PMN-MDSCs are induced by multiple myeloma-related mesenchymal stem cells to have high expression of ARG1 and exert immunosuppressive function in tumor [103] Multiple myeloma PMN-MDSCs limit the anti-tumor response of T cells by increase the expression of ARG1 and other suppressive molecules, which is correlated with the expression of IL-18 [104] Head and neck cancer and urological cancers Overexpression of fatty acid transport protein 2 (FATP2) in PMN-MDSCs is conductive to tumor growth by the synthesis of PGE2 [29] Lymphomas are malignant tumors derived from the lymphatic hematopoietic system and are divided into Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL) [106]. Several studies have uncovered that in NHL, including B cell NHL, diffuse large B cell lymphoma and NK/T cell NHL, increased expression of ARG1, IDO and iNOS in MDSCs is relevant to the enhancement of tumor growth and suppression of T cells [107][108][109][110].…”
Section: Arg1mentioning
confidence: 99%